INCARCERATED WOMEN: A STUDY OF SEXUAL AND REPRODUCTIVE RIGHTS IN THE SISTER ZORZI WOMEN’S PENAL ESTABLISHMENT - Torres, Rafael Eichler; Tonhá, Eduardo Nogueira; Vanderlei, Isis Avon Carolino; de Moraes, Rebeca Massaneiro; e Silva, Tiago Andreotti; Duarte, Sebastião Junior Henrique (Seven Editora, 2025)
The article aims to verify whether there is any type of violation of the sexual and reproductive rights of women deprived of liberty in Mato Grosso do Sul. Sexual and reproductive health is considered as the physical, emotional, mental and social well-being related to sexuality and reproduction, without conditioning procreation. With regard to the population detained in penal establishments, Brazilian legislation provides for conjugal visits, subject to compliance with the requirements established in Resolution No. 23/2021, of the National Council for Criminal Policy. Even if there is regulation, the legal framework is not sufficient for the detained person to be contemplated with the right to exercise their sexual health. The text discusses the deficiencies in the physical structures of cells and other reserved spaces, as well as possible gender inequality. It is concluded that there is a possible violation of sexual and reproductive rights for the majority of women deprived of liberty, considering that only the minority receives conjugal visits, which can be exacerbated by deficiencies in cell structures, which do not have a place reserved for sexual contact, as well as by the legislation that regulates conjugal visits. which is quite restrictive. DOI: https://doi.org/10.56238/sevened2025.018-021